As per given by the question,
There are given that focus point at (6, 2) and line y=0.
Now,
Distance from line dL=distance from the point dF
Then,
![y=\sqrt[]{(x-x_1)^2+(y-y_1)^2^{}_{}}^{}](https://img.qammunity.org/2023/formulas/mathematics/college/9sfsorddccsr9qhhj4cwchfu9xh68ux1jh.png)
Now,
![\begin{gathered} y=\sqrt[]{(x-x_1)^2+(y-y_1)^2^{}_{}}^{} \\ y=\sqrt[]{(x-6)^2+(y-2)^2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zj8wddbhinxnp8iggdblchv97lbdmxysky.png)
Then,
Square on the both side of the equation,
![\begin{gathered} y^{}=\sqrt[]{(x-6)^2+(y-2)^2} \\ y^2=(x-6)^2+(y-2)^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rj03dwopmbode35kffvgza8s98d7x526m0.png)
According to the question,
There are given that y=0,
So,
![\begin{gathered} y^2=(x-6)^2+(y-2)^2 \\ y^2=x^2+36-12x+y^2+4-4y \\ y^2=x^2+y^2-12x-4y+40 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x8fl9yatx71emarkl8mwm0g7ae6il7430f.png)
Now,
![\begin{gathered} x^2-12x-4y+40=0 \\ x^2-12x+40=4y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9ouxg8h3ikgfdy4yp4621zsepok6kd11gi.png)
Now, find the value of jy from above equation;
![\begin{gathered} 4y=x^2-12x+40 \\ y=(1)/(4)(x^2-12x+40) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sn9duqdccshwxpzy8okavayyi7jxx5eh6q.png)
So,
![\begin{gathered} y=(1)/(4)((x-6)^2+4) \\ y=(1)/(4)(x-6)^2+1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b7x8e68bd5i63py9djxfob7ekvpkc7o9ya.png)
Hence, the option D is correct.